The Rule Of Law, The Constitution, And Democracy In In-donesian State Administration Practice - Haryoko Bambang Widjayanto; Yoga Tri Hartanto (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Indonesia constitutionally declares itself as a state based on the rule of law as mandated in Article 1 paragraph (3) of the 1945 Constitution after the amendments. This principle requires that governance and law enforcement be conducted under constitutional supremacy, legal certainty, equality before the law, and an independent judiciary. However, various political interferences, regulatory inconsistencies, and discriminatory legal practices continue to undermine these ideals. This research examines: (1) the effectiveness of the hierarchy of legislation and judicial review mechanisms by the Constitutional Court (MK) and the Supreme Court (MA) in preventing regulatory conflicts and discriminatory law enforcement; and (2) the extent to which the rule of law principle post-amendment has been manifested in equal protection before the law and judicial independence. Using a normative legal research method with statute, conceptual, case, and historical approaches, this study finds that although constitutional reforms have strengthened checks and balances and judicial authority, the persistence of selective and politically influenced law enforcement indicates that equality before the law has not been consistently implemented. Strengthening institutional integrity, improving regulatory harmonization, and ensuring the judiciary’s independence remain crucial to realizing Indonesia’s constitutional aspirations as a democratic state governed by the rule of law.